Genome-Wide Survey of Leucine-Rich Repeat Receptor-Like Protein Kinase Genes and CRISPR/Cas9-Targeted Mutagenesis BnBRI1 in Brassica napus - Song, Min; Linghu, Bin; Huang, Shuhua; Li, Fang; An, Ran; Xie, Changgen; Zhu, Yantao; Hu, Shengwu; Mu, Jianxin; Zhang, Yanfeng (Frontiers in Plant Science, 2022)
The leucine-rich repeat receptor-like protein kinase (LRR-RLK) family represents the largest group of RLKs in plants and plays vital roles in plant growth, development and the responses to environmental stress. Although LRR-RLK families have been identified in many species, they have not yet been reported in B. napus. In this study, a total of 444 BnLRR-RLK genes were identified in the genome of B.napus cultivar ‘Zhongshuang 11’ (ZS11), and classified into 22 subfamilies based on phylogenetic relationships and genome-wide analyses. Conserved motifs and gene structures were shared within but not between subfamilies. The 444 BnLRR-RLK genes were asymmetrically distributed on 19 chromosomes and exhibited specific expression profiles in different tissues and in response to stress. We identified six BnBRI1 homologs and obtained partial knockouts via CRISPR/Cas9 technology, generating semi-dwarf lines without decreased yield compared with controls. This study provides comprehensive insight of the LRR-RLK family in Brassica napus. Additionally, the semi-dwarf lines expand the ‘ideotype’ germplasm resources and accelerate the breeding process for Brassica napus.